Analisis Peran KSOP Kelas II Gresik Dalam Menunjang Keselamatan dan Keamanan Kapal di Wilayah DLKr Gresik - Dwi Perkasa, Andika Tunas; Nofandi, Faris; Ratnaningsih, Dyah; Arisusanty, Dian Junita (Innovative: Journal Of Social Science Research, 2025)
Indonesia is the largest archipelagic country in the world with over 17,000 islands, making maritime safety an essential aspect. In port management, there are two main regions, namely DLKr (Port Work Environment Area) and DLKp (Port Interest Area). KSOP Class II Gresik, as the technical implementation unit of the Ministry of Transportation, is responsible for overseeing ship safety and security. Based on the Maritime Court data from 2018–2024, there were 198 ship accidents with 158 fatalities, indicating weaknesses in safety supervision. This study aims to analyze the influence of KSOP's role on ship safety and security management in the DLKr area of Gresik. The method used is a quantitative approach with simple linear regression analysis through SPSS. The respondents consisted of 50 people from ship crews and harbor officers, using quota sampling technique. The results show that t count (2.701) > t table (2.010) and a significance of 0.010 < 0.05, indicating that KSOP's role has a significant effect. The regression equation Y = 1.321 + 0.525X shows a positive influence, although the R² value of 13.2% indicates that its impact is still limited. Pearson’s correlation of 0.363 shows a significant but weak to moderate relationship, suggesting that the effectiveness of supervision still needs improvement.